Coping Strategies and Tactics to Deal With Social Vulnerability in the Flood Disaster of March 25, 2015, in Chañaral and Diego de Almagro, Chile - Pérez Tello, Sonia; Aldunce Ide, Paulina; Flores-Haverbeck, Fernanda; Mena Maldonado, Dania; Castro Correa, Carmen Paz; Wyndham Vásquez, Katherine (Frontiers in Climate, 2022)
A socio-natural disaster event exacerbates pre-existing socio-economic crises and disrupts the life projects of the people affected, generating the deployment of strategic or tactical actions to deal with it. When societies have populations living in conditions of social vulnerability prior to disasters, such actions are more complex and difficult to manage. On March 25, 2015 (25M), the inhabitants of the towns of Chañaral and Diego de Almagro, in the Atacama Region of Chile, were faced with a flood that produced a crisis of great magnitude. This qualitative research describes the actions the inhabitants used to reduce social vulnerability, before, during and after the emergency. These actions were analyzed to describe the extent of planning, meanings, resources and structures of opportunities present in the actions. Content analysis was carried out on semi-structured interviews with 38 affected people, selected using intentional sampling technique together with snowball sampling. Subjective resources were identified: sense of family, solidarity, autonomy and restitution of rights. The superimposed mobilization of these resources resulted in a complex situation of resilience. It is concluded that the way of learning actions includes family and cultural habits, daily learning and previous experiences, and imitation, among others. Recommendations are made to be considered for the reduction of risks of socio-natural disasters. Specifically, policies that include educational strategies that are based on the ways of acting shown by the communities.